Os multiterritórios da Igreja Católica em Maceió-AL - Carvalho, Bruno Leandro Freitas de (2024)
The process of formation of the territories of the Catholic Church in Maceió followed the same parameter of ecclesiastical spatialization on a global scale. The analysis of this phenomenon presupposed its geographical, historical and culturally contextualized understanding and this theme has gained notoriety in studies in the area of Geography of Religion. The research was delimited as a general objective, to analyze the multiterritories of the Catholic Church, considering its geo-historical performance in the urban space of the capital of Alagoas and, specifically, to understand the process of spatialization of the Archdiocese of Maceió; identify the distribution of parishes in the urban fabric of Maceio; understand the practices of parish movements; discuss the strategies of the Catholic Church for maintaining its territories. In this sense, to understand the domain, control and maintenance of the territories of the Catholic Church, we based our research on the contributions of Haesbaert (2004); Saquet (2003) and Rosendahl (2008). We adopted qualitative research, bibliographic and documentary research and interviews as methodological procedures. Therefore, we address the different scales of action of the Archdiocese of Maceió, based on the case study of the Metropolitan Cathedral of Nossa Senhora dos Prazeres, considering its constitution, as well as daily and parish community life seen as the path in faith. We understand that the construction of territory is the result of the process of appropriation and production/domination of a space, inscribing itself in a field of power, economic, political and cultural relations. And, that territorialities are strengthened by the collective or individual religious experiences of a group with the sacred place and the itineraries that constitute its territory.